Structure-activity relationships of carbapenems that determine their dependence on porin protein D2 for activity against Pseudomonas aeruginosa. - Fung-Tomc, J C (1995)
A number of carbapenem derivatives were examined to determine the structure-activity relationships required for dependence on porin protein D2 for activity against Pseudomonas aeruginosa. As suggested by J. Trias and H. Nikaido (Antimicrob. Agents Chemother. 34:52-57, 1990), carbapenem derivatives, such as imipenem and meropenem, containing a sole basic group at position 2 of the molecule utilize the D2 channel for permeation through the outer membrane of pseudomonads; they are more active against D2-sufficient strains of P. aeruginosa. Our results indicated that carbapenems with a basic group at position 1 or 6 of the molecule did not depend on the D2 channel for activity; i.e. they were equally active against D2-sufficient and D2-deficient pseudomonal strains. However, addition of a basic group at position 1 or 6 of a carbapenem derivative already containing a basic group at position 2 resulted in its lack of dependency on the D2 pathway. Comparison between meropenem and its 1-guanidinoethyl derivative, BMY 45047, indicated that they differed in their dependence on D2; while meropenem required the D2 channel for uptake, BMY 45047 activity was independent of D2. Meropenem and BMY 45047 had similar affinities for the penicillin-binding proteins of P. aeruginosa. However, BMY 45047 and meropenem differed in the morphological changes that they induced in pseudomonal cells. While meropenem induced filamentation, BMY 45047 induced filaments only in BMS-181139-resistant mutants and not in imipenem-resistant mutants or in carbapenem-susceptible P. aeruginosa strains. These results suggested that in Mueller-Hinton medium the uptake of BMY 45047 through the non-D2 pathway is more rapid than that of meropenem through the D2 porin. In summary, the presence of a basic group at position 2 of a carbapenem is important for its preferential uptake by the D2 channel. However the addition of a basic group at position 1 or 6 of a carbapenem already containing a basic group at position 2 dissociates its necessity for porin protein D2 for activity.